The Influence of Fear of Missing Out (FOMO), Social Media Exposure, and Risk Tolerance on Cryptocurrency Investment Intentions - Muhammad Amsal Nasution; Latifa Dinar Rahmani; Ingrid Panjaitan; Eko Meiningsih (Malaqbi Publisher, 2026)
This study aims to examine the influence of Fear of Missing Out (FOMO), social media exposure, and risk tolerance on cryptocurrency investment intentions. The rapid growth of cryptocurrency markets, combined with the increasing role of digital platforms, has shifted investment behavior toward more psychologically and socially driven decision-making. This research employs a quantitative approach using a cross-sectional survey design, with data collected from individuals who are familiar with or interested in cryptocurrency investments. A total of 200 respondents were selected using purposive sampling, and data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The results indicate that FOMO, social media exposure, and risk tolerance all have a positive and significant effect on cryptocurrency investment intention. Among these variables, social media exposure is found to have the strongest influence, highlighting the critical role of online platforms in shaping investor perceptions and behavior. FOMO also significantly drives investment intention by triggering emotional responses and urgency, while risk tolerance reflects individuals’ willingness to engage in high-risk financial activities. The model demonstrates strong explanatory power, suggesting that these variables collectively provide a comprehensive understanding of cryptocurrency investment behavior. This study contributes to the behavioral finance literature by integrating psychological, social, and individual factors in the context of digital investments. The findings offer practical implications for investors, policymakers, and financial educators to promote more informed and rational investment decisions in the evolving cryptocurrency landscape.